Pharmacokinetics of Recombinant Factor VIIa in the Rat – A Comparison of Bio-, Immuno- and Isotope Assays - Thomsen, Mads Krogsgaard; Diness, Viggo; Nilsson, Povl; Rasmussen, Søren Nørgaard; Taylor, Trevor; Hedner, Ulla (Thrombosis and Haemostasis, 1993)
Recombinant human factor VII a (rFVIIa) is an activated coagulation factor for intravenous use as a haemostatic agent in haemophiliacs who generate antibodies against factor VIII or IX. Plasma kinetic studies are important for the understanding of the action of rFVIIa which is exerted in the vascular compartment of the body, more specifically on the vessel walls at the site of injury. In the present study, rats were dosed 100 or 500 μg/kg 125I-rFVIIa i. V., without any side effects being observed, and the plasma profile of rFVIIa was studied by 3 different assays that were shown to correlate well at early times post-dose: trichloroacetic acid (TCA)-precipitable drug-related radioactivity, rFVIIa antigen determination by ELISA technique, and the assay of clot activity which is the only clinically applicable assay. The plasma concentration curve could be resolved into 1-3 exponentials, depending on the FVIIa detection principle that was employed. Initially, there was a short (ca. 10 min) phase of increasing concentrations before the attainment of Cmax. This was followed by a plasma recovery (Cmax × plasma volume/dose) in the vicinity of one half of the administered dose. The initial volume of distribution (V1) corresponded to the vascular compartment whereas the volume of distribution at steady state (Vss) was somewhat larger. Whole body clearance (CL-B) of rFVIIa was approx. 1 ml/min per kg, and mean residence time (MRT) and the half-life assumed to be associated with the loss of biological activity was approx. 1 h and 20-45 min, respectively. From these plasma data, rFVIIa appears to be a low clearance compound with limited tissue distribution and a short half-life. Tissue distribution studies showed that high 125I levels, assumed to be rFVIIa-related, included mineralised bone and well-perfused organs such as the liver which suggested that this organ was responsible for a major proportion of CL-B. Finally, mass balance studies showed that almost 90% of the administered radioactivity could be accounted for following an i. v. dose, predominantly as non drug-related radioactivity, even though a small amount of TCA-precipitable radioactivity was excreted via the biliary route. In conclusion, dose- or sex-dependent plasma kinetics and tissue distribution within a dose range of 100 to 500 μg/kg of rFVIIa was not observed. In the early and pharmacologically relevant phase after rFVIIa administration there appears to be good agreement between the various plasma assays employed in the study, indicating that the clot assay yields useful information in studies of rFVIIa plasma pharmacokinetics.